IDDF2018-ABS-0231 Acidosis promotes the stemness of cancer stem cells through vitamin d-vitamin d receptor signalling pathway in colorectal cancer. (June 2018) - Hu, Peishan; Li, Ting; Ju, Huaiqiang; Xu, Ruihua
Abstract : Background: The tumour recurrence, metastasis and treatment resistance of colorectal carcinoma (CRC) are closely related to acidic tumour microenvironment and colorectal cancer stem cells (colorectal CSCs). Here we identified the regulatory effects of the acidic tumour microenvironment on vitamin D receptor (VDR) and the regulation of the signal axis on the self-renewal of colorectal stem cells. Methods: Using western blotting and relative quantitative PCR to detect VDR expression in 43 pairs of normal and CRC samples and acidic condition. Self-renewal ability of colorectal CSCs was detected by sphere formation assay, limited dilution assay and flow cytometry. Chromatin immunoprecipitation, gain of function and lose of function assay was used to screen the target genes of VDR and their effects on colorectal CSCs. Results: Firstly we found VDR mRNA decreased under acidic condition. And the expression of VDR in CRC tissue compared to adjacent normal tissue was decreased significantly. In addition, the VDR protein expression was the lowest in colorectal CSCs compared to normal, and CRC cells, VDR expression in colorectal cancer cells with strong metastatic ability was also reduced. Over-expressing VDR in CRC sample cell line resulted in decreased cell migration and invasion ability. The proportion of PROM1 (prominin 1) positive cells decreased when over-expressed VDR in colorectal CSCs, the number and size of spheres formed by cells were markedly reduced and the sphere cells differentiated and generated processes. While knockdown of VDR in CRC cells resulted in the elevated proportion of PROM1 positive cells, increased number and size of spheres and elevated expression of SOX2 (SRY-box 2). We also found that VDR was combined with the promoter region of SOX2 and POU5F1 (POU class 5 homeobox 1), which contained vitamin D response elements, in a series of stem cell markers. Conclusions: Acidic tumour microenvironment may regulate vitamin D signalling pathway by lowering the expression of VDR. VDR inhibited the invasion, metastasis and cancer stem cell phenotype of CRC cells through interacting with the promoter of SOX2 and POU5F1 . Suggesting normalising tumour microenvironment and combined use of vitamin D and chemotherapeutic drugs are a potentially effective strategy in the treatment of CRC.